ChemInform Abstract: Ruthenium(II)/N‐Heterocyclic Carbene Catalyzed [3 + 2] Carbocyclization with Aromatic N—H Ketimines and Internal Alkynes. Issue 45 (14th October 2013) - Zhang, Jing; Ugrinov, Angel; Zhao, Pinjing
Abstract A Ru‐catalyzed [3 + 2] annulation between NH‐ketimines and internal alkynes is developed to give indenamine derivatives in good yields.